Features of the Canoeists' Special Physical Fitness at the Distance of 1000 m - Pengcheng Guo; Ziyang Zhang; Zijian Huang; Xianglin Kong; Andrii Diachenko; Olga Rusanova; Andrey Rusanov (OVS LLC, 2022)
The aim of the study. To better understanding of the indicators of functional support for special endurance and physiological demands in canoeists at a distance of 1000 m.  Material and methods: 20 athletes (19-23 years) in canoeing from Shandong and Jiangxi provinces.  Results. According to the results of the analysis, the following typological groups of athletes-canoeists, specializing in the distance of 1000 m, with pronounced differences in the implementation of anaerobic energy supply. Typological groups of athletes had no significant differences in aerobic energy capacity (p > 0.05).  The first typological group (La max 90s <10.08 mmol·l-1, p < 0.05) is characterized by: power indicators 4.96 ± 2.35 mmol·l-1 and anaerobic energy supply capacity 6.93 ± 3.16 mmol·l-1, which were the lowest among other groups of athletes. Athletes showed significantly low performance in 10-s, 30-s and 90-s tests, and performed less work in the step test, with varying degrees of severity of fatigue compensation mechanisms.  The second typological group (La max 90s - 10.08-16.64 mmol·l-1, p < 0.05), is characterized by high power 7.4 ± 1.68 mmol·l-1 and low capacity anaerobic energy supply 13.32 ± 1.52 mmol·l-1. Athletes performed a sufficient amount of work in the step test (3-4 steps), but performance in the 90-s test was reduced, there were reduced characteristics of the ability to compensate for fatigue. The third typological group (La max 90 c-> 16.64 mmol·l-1, p <0.05) is characterized by: power indicators 8.20 ± 2.36 mmol·l-1  and anaerobic energy supply capacity 17.85 ± 1.05 mmol·l-1, which were the highest among other groups of athletes and significantly (p < 0.05) higher performance in 30-s, 90-s tests, and the level of power at which the maximum oxygen consumption in the step test is reached.  Conclusion. The results of the studies indicate differences in the level of functional support for special endurance for paddlers of uniform groups for canoeists that specialize in a distance of 1000 m.